The care provided by health teams at airports: phenomenological focus (Research, Society and Development, 2020)
The study aims to identify in the literature the care provided by different health teams that work in the airport environment under a phenomenological approach. Qualitative methodological approach and integrative literature review. The databases: BDENF, CINAHL, IBECS, LILACS, MEDLINE, SCOPUS and PubMed were searched. The research question was elaborated with the aid of the PICo strategy (Population: Health team; Intervention: care; Context: Airports). The search was carried out between April and May 2019. The review included national and international articles, with abstracts and full texts, in Portuguese, Spanish and English, in a time frame between the years 2014 to 2019. Twelve studies were included that revealed the care provided to patients at the airport by the health team and pre-trip preventive measures. The care provided to patients at the airport by the health team aims at preventive pre-trip measures and emergency care with safety. They refer to the perception of the professional, with their experiences and care that is above all humanized and ethical, aiming not only at taking care of technical acts but at maintaining life.